2022
DOI: 10.5603/fm.a2021.0008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the therapeutic effects of bone marrow mesenchymal stem cells versus platelet rich plasma on the pancreas of adult male albino rats with streptozotocin-induced type 1 diabetes mellitus

Abstract: This article has been peer reviewed and published immediately upon acceptance. It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…GIIb showed a significant increase in Mean of the diameter of the islet when compared with GIIa. These results were consistent with (18,29,30) and there was a significant decrease in FBG level, area % of caspase 3, and collagen fibers as compared with GIIa this agreed by (5,31,32) who explained that pancreatic fibrosis may be caused by pancreatic stellate cells that have been activated by hyperglycemia, resulting in fibrotic changes. Group IIc had a significant increase in the mean diameter of islets and a significant decrease change in FBG level, collagen fibers, and caspase 3 immune reactivity as compared with GIIa and GIIb.…”
Section: Discussionsupporting
confidence: 85%
“…GIIb showed a significant increase in Mean of the diameter of the islet when compared with GIIa. These results were consistent with (18,29,30) and there was a significant decrease in FBG level, area % of caspase 3, and collagen fibers as compared with GIIa this agreed by (5,31,32) who explained that pancreatic fibrosis may be caused by pancreatic stellate cells that have been activated by hyperglycemia, resulting in fibrotic changes. Group IIc had a significant increase in the mean diameter of islets and a significant decrease change in FBG level, collagen fibers, and caspase 3 immune reactivity as compared with GIIa and GIIb.…”
Section: Discussionsupporting
confidence: 85%
“…This was also observed in the free control though, and can therefore not be attributed to the bioprinting but is more likely an artefact of batch variation. While other research has indicated that especially PRP can lead to the increased proliferation of pancreatic (β-)cells in vivo [ 40 , 62 ], we detected a positive influence of FFP-supplementation at early time points but not of PL-supplementation, despite mostly similar compositions. On the other hand, during in vivo studies, PRP was injected twice weekly and proliferation was seen in adult rats [ 40 , 59 ], whereas supplements were released from bioinks over time and not replenished.…”
Section: Discussioncontrasting
confidence: 78%
“…For rat islets in vitro, this resulted in an increased viability, as well as an increased insulin content and release with no reported SI [ 59 ]. In vivo, when diabetes was induced in rats, the injection of PRP led to an increase in the number of β-cells, increased insulin secretion, improved blood-glucose control, and reduced oxidative stress [ 40 , 41 , 59 , 62 ]. A positive effect on the number of β-cells was also observed when PRP was added during the differentiation of induced pluripotent stem cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in blood glucose levels and lesions in renal tissue [ 94 ] 1 UC-MSC Decrease in blood globulin and platelet level. Decrease in erythrocyte sedimentation rate, C-reactive protein level, and rheumatoid factor [ 95 ] 2 UC-MSC Decrease in Desease Activity Score-28. Decrease in IL-6 and increase in IL-10.…”
Section: Introductionmentioning
confidence: 99%
“…BM-MSCs were shown to be a better treatment than platelet-rich plasma injection in T1D rat model. The results showed that the group treated with BM-MSCs had an increase in the diameter of Langerhans islets and the amount of zymogen granules compared to the untreated group and the group treated with platelet-rich plasma [ 95 ]. A study tested the immunomodulatory capacity and beta cell protection of Ad-MSCs in a diabetic mice model.…”
Section: Introductionmentioning
confidence: 99%